Body dissatisfaction as an explanatory variable of eating disorders - Maganto Mateo, Carmen (2002)
Eating disorders ha ve increased over the last few years, as well as the age range of their initialonset which includes younger people. Food-related anxiety, fear of gaining weight, and obsession with thinness are associated with variables of age, sex, social leve!, body mass index, distortion and dissatisfaction with body image are considered risk factors for eating disorders. This research examined the relationship among these factors and analyzed their predictive value. The participants were 200 adolescents (104 boys and 96 girls), aged between 14 and 17 years. The testsused werc the STAI, EDI-2, EAT and two experimental tests. The results indicated that underlying these disorders were distorted body-image perception and dissatisfaction. The risk for girlsincreased between 15 and 16 years. Dissatisfaction with global physical aspect, distortion of body size, age, and trait anxiety were revealed as predictive factors.